Umiejętność wykorzystywania czasu warunkiem sukcesu zawodowego - Smolbik-Jęczmień, Alicja (Time management skills as a precondition for professional success, 2007)
The article presents the role of knowledge of methods and principles of time management in the opportunity for professional success achievement. A special attention is paid to the following questions: factors determining professional success, basie methods of time management, indentifleation of so-called “time-wasters”, and the ways to fight them as well as the most important benefits of competent time management. The article also consists of research results conceming the use of work time by managers in Poland and abroad.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 243-252